Release characteristics and mechanisms of sediment phosphorus in contaminated and uncontaminated rivers: A case study in South China. (1st January 2021) - Li, Rui; Gao, Lei; Wu, Qirui; Liang, Zuobing; Hou, Lei; Yang, Zhigang; Chen, Jianyao; Jiang, Tao; Zhu, Aiping; Li, Manzi
Abstract: Phosphorus (P) cycling present in sediments associated with iron (Fe), manganese (Mn) and sulfur (S) geochemical processes may cause secondary pollution in overlying water. Understanding the mechanisms of P release from sediments should help to restore water quality. This study used the diffusive gradients in thin film (DGT) technique to investigate the seasonal variation in the lability, remobilization mechanisms, and release characteristics of sediment P in the uncontaminated Xizhi River and the severely contaminated Danshui River, South China. P accumulation in sediments contributed to higher DGT-labile P concentrations in contaminated reaches, and the highest labile P concentrations were generally observed in summer season at each site. The significant positive relationships ( p < 0.05) between labile Fe and P confirmed the Fe–P coupling release mechanism in uncontaminated sediments. Stronger relationships between labile Mn and P at contaminated sites indicated that Mn oxides played an important role in P remobilization. However, sulfate reduction associated with microbial activities (crucial genera: Desulfobulbus, Desulfomicrobium and Desulforhabdus ) was considered to decouple the Fe & Mn–P cycling relationship, promoting P release at contaminated sites. The effluxes of sediment P were much higher in the Danshui River (mean 0.132 mg cm −2 ·d −1 ) than in the Xizhi River (mean 0.038 mg cm −2 ·d −1 ). And hot season led to growth in P effluxes that was much greater in contaminated river. Graphical abstract: Image 1 Highlights: Fe–P coupling release was the major mechanism leading to remobilization of sediment P. Reductive dissolution of Mn oxides was responsible for P release in polluted sediment. Sulfate reduction related to specific microbial activity triggered decoupling Fe/Mn–P. Upward diffusion fluxes of P and Fe were greater at polluted sites in summer seasons.